History as an Image: Ecranisation of King Danylo Romanovych - Nazarii Khrystan (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2017)
The formation of the Soviet image of the past in the context of the doctrine of «our great ancestors» was extended not only to historiography, fiction and journalism. A special place was occupied by cinema. The Bolsheviks were very early realized the tremendous role of cinema as a means of influencing mass culture. With the help of cinema, the party leadership sought to form a «true» view of reality, thereby educating people in the spirit of «communism and internationalism». Founded in the early 30’s oftheXX century. the genre of historical cinema, became the basis of all Soviet cinema. Rejecting the leading role of the «masses» in the tapes, bolsheviks turn to the biography of outstanding and «progressive» historical personalities, first of all, rulers and generals. Throughout the period of existence of Soviet cinema, the historical biographies of Alexander Nevsky, Ivan the Terrible, Peter I, Michael Kutuzov, Alexander Suvorov and others were filmed. The most important document of the memory of Danylo Romanovich in the era of Soviet patriotism was the film of Ukrainian director Yaroslav Lupiya – «Danylo – Prince Galician». The Film was created in 1987 at the Odessa Film Studio named after O. Dovzhenko. Before us is a work that was supposed to create a stable image of Prince Danylo Halytsky in the consciousness of Ukrainian society. The image is dictated «from above». The ecranisation of Danylo Romanovych requires a detailed study of not only the history of the film, but also the reception of the ruler in the Soviet image. This will allow us to trace and analyze the struggle for the appropriation and stylization of the image in detail, as well as contradictory directions in forming the concept of the «Soviet patriot» of Danylo Halytsky.